The membrane transporter SLC25A48 enables transport of choline into human mitochondria - Patil, Suraj; Borisov, Oleg; Scherer, Nora; Wirth, Christophe; Schlosser, Pascal; Wuttke, Matthias; Ehret, Sandra; Hannibal, Luciana; Eckardt, Kai Uwe; Hunte, Carola; Neubauer, Björn; Köttgen, Anna; et al. (Kidney International, 2024)
Choline has important physiological functions as a precursor for essential cell components, signaling molecules, phospholipids, and the neurotransmitter acetylcholine. Choline is a water-soluble charged molecule requiring transport proteins to cross biological membranes. Although transporters continue to be identified, membrane transport of choline is incompletely understood and knowledge about choline transport into intracellular organelles such as mitochondria remains limited. Here we show that SLC25A48 imports choline into human mitochondria. Human loss-of-function mutations in SLC25A48 show impaired choline transport into mitochondria and are associated with elevated urine and plasma choline levels. Thus, our studies may have implications for understanding and treating conditions related to choline metabolism.
CRIS-Team Scopus Importer:2024-08-23
Keywords: choline transport; deorphanization; mGWAS; mitochondria; SLC25A48